Migration of Rural Residents in Russia’s Regions: Issues, Trends, and Focus Areas - S. Kovanova, E.; V. Badmaeva, N. (International Journal of Engineering and Technology, 2018)
This paper relies on statistical information to investigate the relevant issue of rural migration across Russia’s federal districts. Migration by rural residents may lead to declines in the relative share of rural residents in the nation’s social structure, intensify its urbanization processes, cause rural depopulation, and result in declines in the demographic potential of rural areas. These processes are associated with profound social and economic issues facing the Russian countryside.